[Investigation of the prevalance of Demodex folliculorum and Demodex brevis in rosacea patients] - Yücel, Ahmet; Yilmaz, Mustafa (My University, 2013)
[Abstract Not Available]
Rosacea Ön Tanılı Hastalarda Demodex folliculorum ve Demodex brevis Yaygınlığının Araştırılması
Keywords: Adult; Aged; Animals; Cheek; Face; Female; Forehead; Humans; Male; Middle Aged; Mite Infestations; Mites; Rosacea; Skin; Young Adult; adult; aged; animal; cheek; complication; face; female; forehead; human; male; middle aged; mite; mite infestation; parasitology; pathology; rosacea; skin; young adult